COVID-19 and thyrotoxicosis (Actualizaciones en Sida e Infectología, 2021)
The infection by the new severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has challenged the health care system with a new spectrum of clinical manifestations and organ disfuntions, that require proper diagnosis and treatment.In this case we report a patient with persistent tachycardia after COVID-19 acute illness. This finding led to multiple medical visits until final diagnosis of thyrotoxicosis of autoimmune etiology.Thyrotoxicosis is an unusual complication of COVID-19, that results in higher morbility in patients during the convalescent phase of the disease. Opportune clinical suspicion and early diagnosis seems to be beneficial in terms of clinical outcome
Keywords: COVID-19; SARS-CoV-2; Thyrocytes; Thyroid